2019
DOI: 10.3390/molecules24101917
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Extraction Techniques for the Evaluation of Volatile Compounds in Spray-Dried New Zealand Sheep Milk

Abstract: Recent growth and diversification of sheep milk products means more sophisticated methods are required to ensure their flavour quality. The objective of this study was to compare four extraction techniques for the analysis of volatile compounds in sheep milk by gas chromatography-mass spectrometry (GC-MS). Solvent Assisted Flavour Evaporation (SAFE), Solid Phase Microextraction (SPME), Headspace Sorptive Extraction (HSSE) and Stir Bar Sorptive Extraction (SBSE) were evaluated for their sensitivity, selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…The only sulfurcompound identified among the volatile components of fresh milk in the study of (Moio et al, 1993) was dimethyl sulphone. High et al (2019) also noted that the SPME technique enables extraction of this small polar compound, which is consistent with the result of the present study.…”
Section: The Volatile Fingerprint Of Gmp: An Hs-spme-gc-ms Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…The only sulfurcompound identified among the volatile components of fresh milk in the study of (Moio et al, 1993) was dimethyl sulphone. High et al (2019) also noted that the SPME technique enables extraction of this small polar compound, which is consistent with the result of the present study.…”
Section: The Volatile Fingerprint Of Gmp: An Hs-spme-gc-ms Analysissupporting
confidence: 93%
“…However, in the current study, only 2 ester compounds were identified in the New Zealand GMP using the HS-SPME-GC-MS procedure (Table 2). A similar result was reported in the study of High et al (2019), where esters were not found in the spray-dried New Zealand sheep milk. It was suspected that high thermal load from pasteurization to subsequent spray-drying of the milk powder had affected the levels of esters by decreasing or eliminating them in milk.…”
Section: The Volatile Fingerprint Of Gmp: An Hs-spme-gc-ms Analysissupporting
confidence: 89%
“…All DI-HiSorb techniques (DI-HiSorb S and DI-HiSorb NS), independent of GC column polarity, were characterized by the large volume of lactones extracted (>82%), which differs considerably to all of the other extraction techniques. A similar result was found for SBSE, which is a comparable technique to DI-HiSorb that also used PDMS as the sorbent phase [19]. The only other significant number of chemical classes extracted by DI-HiSorb NS were aldehydes, ketones, and furans, but DI-HiSorb NS did not extract any alcohols, sulphur compounds, acids, terpenes, or esters with the non-polar GC column (but did extract low levels, from 0.5-0.63%, with the polar GC column).…”
Section: The Percentage Of Each Chemical Class Extracted From Whole Milk Powder By Each Techniquesupporting
confidence: 77%
“…However, the extensive sample handling during SAFE, reduce the reproducibility of this extraction technique. Moreover, the lack of sampling automation and the long sample preparation time required, are the main reasons explaining the reduced use of DSE-SAFE in the extraction of aroma compounds in truffles [ 96 ].…”
Section: Analytical Methods For the Determination Of Voc In Trufflmentioning
confidence: 99%